Economics of the environment [5th ed.] selected readings - Stavins, Robert N. [ed.] (New York W. W. Norton, 2005)
The readings in this volume-selected for their accessibility, coverage and currency-span the full scope of environmental economics and their authors compromise a veritable Who's Who of the field.
Keywords: Environmental economics; Economics